Feedback inhibition of actin on Rho mediates content release from large secretory vesicles - Segal, Dagan (J Cell Biol, 2018)
Secretion of adhesive glycoproteins to the lumen of Drosophila melanogaster larval salivary glands is performed by contraction of an actomyosin network assembled around large secretory vesicles, after their fusion to the apical membranes. We have identified a cycle of actin coat nucleation and disassembly that is independent of myosin. Recruitment of active Rho1 to the fused vesicle triggers activation of the formin Diaphanous and actin nucleation. This leads to actin-dependent localization of a RhoGAP protein that locally shuts off Rho1, promoting disassembly of the actin coat. When contraction of vesicles is blocked, the strict temporal order of the recruited elements generates repeated oscillations of actin coat formation and disassembly. Interestingly, different blocks to actin coat disassembly arrested vesicle contraction, indicating that actin turnover is an integral part of the actomyosin contraction cycle. The capacity of F-actin to trigger a negative feedback on its own production may be widely used to coordinate a succession of morphogenetic events or maintain homeostasis.